Pengembangan Media Pembelajaran Scrapbook Digital Berbasis Canva pada Materi Teks Negosiasi Siswa Kelas X SMK Negeri 1 Sogaeadu - Warisman Zebua; Lestari Waruwu; Yanida Bu’ulolo; Arozatulo Bawamenewi (Pusat riset dan Inovasi Nasional, 2025)
This study aims to develop a Canva-based Digital Scrapbook as a learning medium for negotiation texts for tenth-grade students at SMK Negeri 1 Sogae'adu. The research uses the Research and Development (R&D) method with the Borg and Gall model, which includes ten steps: identifying problems, collecting data, designing products, validating designs, revising, product testing, revising, usage testing, final revisions, and mass production. The product trial was conducted with 6 students from class X MP 2, and the usage trial with 33 students from class X MP 1. The media was validated by three experts: material, language, and design. Material validation reached a score of 60 out of 60 (100%), language validation scored 40 out of 40 (100%), and design validation showed high feasibility. The practicality of the media, based on student questionnaires, was 91%. Effectiveness was shown by increased post-test scores, with 81% of students meeting the learning completeness criteria. The results indicate that Canva-based Digital Scrapbook media is highly feasible, practical, and effective for learning negotiation texts. This media improves student engagement, concept understanding, and interest. It supports student-centered learning and fits the needs of 21st-century students who prefer interactive, and visual, and creative approaches to understand material better.